Normalizing Plagiarism: An Analysis of Copy-Paste Culture and the Shifting Values of Academic Honesty in the Era of Artificial Intelligence (AI) - I Wayan Gama (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
This study aims to explore the shift in students' ethical paradigms regarding the use of Generative Artificial Intelligence (AI) and its relationship to the phenomenon of plagiarism. Using a qualitative approach with the theoretical frameworks of Jean Baudrillard's Simulacra and Pierre Bourdieu's Habitus, this study examines how AI technology is changing the nature of scientific work. The results show the normalization of AI use as a new "digital habitus," where 83% of students consider AI a legitimate research tool, but on the other hand, it creates a condition of "Aesthetics Without Substance." The main findings reveal a reduction in originality where academic honesty is only measured through technical scores (such as Turnitin), rather than intellectual depth. The comparison between authentic and AI-based writing indicates the risk of systemic intellectual atrophy. In conclusion, this study recommends the need for a redesign of educational evaluation systems that focus on processes and verbal dialectics to mitigate the impact of pseudo-competence on college graduates.